Vps26p, a Component of Retromer, Directs the Interactions of Vps35p in Endosome-to-Golgi Retrieval - Reddy, Jonathan V. (The American Society for Cell Biology, 2001)
Endosome-to-Golgi retrieval of the carboxypeptidase Y receptor Vps10p is mediated by a recently discovered membrane coat complex termed retromer. Retromer comprises five conserved proteins: Vps35p, Vps29p, Vps5p, Vps17p, and Vps26p. Vps35p recognizes cargo molecules such as Vps10p and interacts strongly with Vps29p. Vps5p forms a subcomplex with Vps17p and has been proposed to play a structural role by self-assembling into large multimeric structures. The function of Vps26p is currently unknown. We have investigated the role that Vps26p plays in retromer-mediated endosome-to-Golgi transport by analyzing dominant negative alleles of Vps26p. These mutants have identified a crucial region of Vps26p that plays an important role in its function. Functional domains of Vps26p have been investigated by the creation of yeast-mouse hybrid molecules in which domains of Vps26p have been replaced by the similar domain in the protein encoded by the mouse VPS26 gene, Hβ58. These domain swap experiments have shown that Vps26p promotes the interactions between the cargo-selective component Vps35p and the structural components Vps5p/Vps17p.